England first, America second: The ecological predictors of life history and innovation. (2019) - Luoto, Severi; Rantala, Markus J.; Krams, Indrikis
Abstract: We present data from 122 nations showing that Baumard's argument on the ecological predictors of life history strategies and innovation is incomplete. Our analyses indicate that wealth, parasite stress, and cold climate impose orthogonal effects on life histories, innovation, and industrialization. Baumard also overlooks the historical exploitation of other nations which significantly enlarged the "pooled energy budget" available to England.